GEOLOGY OF KENDANG VOLCANO WEST JAVA BASED ON IMAGE ANALYSIS USING ALOS 2 PALSAR 2 AND FIELD OBSERVATION - Syarief, Iqbal
Geological mapping on the area with steep topography and high dense of vegetation has a high level of difficulty. One of the methods that can be applied to support geological mapping is using remote sensing method. Satellite images used in this research are Advanced Land Observing Satellite (ALOS) 2 Phase Array Type L-Band Synthetic Aperture Radar (PALSAR) 2 because it has 22.9 cm (L-Band) on its wavelength that able to penetrate the vegetation canopy and it is not limited by the weather or acquisition time. This research is aimed to identify the geological setting using ALOS 2 PALSAR 2 that proved with the geological mapping. The research was done in Kendang Volcano, Bandung regency and Garut regency, West Java. Stratigraphy in the research area divided into Khuluk Kendang and Khuluk Papandayan and divided into 11 units of lithology. In the study area, Khuluk Kendang consisted of three Gumuk, namely Gumuk Jaya, Gumuk Cigangsa, and Gumuk Darajat. Khuluk Papandayan just consist of Gumuk Puntang. Geological structure in the study area form a Dextral Fault near Darajat and Puntang area that showed by presence of altered rocks, springs, and fumaroles. Field observation result supported by petrography analysis showed that lithology in the study area consisted of andesite, pyroclastic breccia, tuff breccia, and tuff lapilli. Composite RGB: HV HH VV shows a red color indicated dense vegetation area, green coor indicates short vegetation area, and blue color indicates wetlands area. Resistant lithology shows a rough relief characterized by bright white hue while less resistant lithology shows a subtle relief characterized by a darker hue in ALOS 2 PALSAR 2. Magnetic susceptibility measurement show that lava product have susceptibility values more than 10 × 10-3 whereas in pyroclastic product having a susceptibility values less than 10 × 10-3.